On two new types of statistical convergence and a summability method - doi: 10.4025/actascitechnol.v36i1.16206 - Dutta, Hemen; Reddy, Bokka Surender; Jebril, Iqbal Hamzah (Acta Scientiarum. Technology, 2014)
In this paper, we introduce and investigate relationship among I-statistically Delta_r^s -convergent, I-lambda-statistically Delta_r^s-convergent and I-[V, lambda, Delta_r^s]-summable sequences respectively over normed linear spaces Â Â Â Â Â